Disruption of IL-17-mediated immunosurveillance in the respiratory mucosa results in invasive Streptococcus pyogenes infection - Mills, Jamie-Lee; Lepletier, Ailin; Ozberk, Victoria; Dooley, Jessica; Kaden, Jacqualine; Calcutt, Ainslie; Huo, Yongbao; Hicks, Allan; Zaid, Ali; Good, Michael F.; Pandey, Manisha (Frontiers in Immunology, 2024)
Streptococcus pyogenes is a Gram-positive pathogen that causes a significant global burden of skin pyoderma and pharyngitis. In some cases, infection can lead to severe streptococcal invasive disease. Previous studies have shown that deficiency of IL-17 in mice (IL-17-/-) can reduce S. pyogenes clearance from mucosal surfaces. However, the impact of IL-17 in the development of severe invasive streptococcal disease has not yet been assessed. Here, we model single or repeated non-lethal, intranasal (IN) S. pyogenes M1 strain infections in immunocompetent and IL-17-/-mice to assess bacterial colonization following a final IN or skin challenge. Immunocompetent mice that received a single S. pyogenes infection showed long-lasting immunity to a subsequent IN infection, and no detection of bacteria in the lymph nodes or spleens. However, in the absence of IL-17, a single IN infection resulted in the dissemination of S. pyogenes to cervical lymph nodes and spleen, which was accentuated by repeated IN infections. In contrast to what was observed at the respiratory mucosa, skin immunity did not correlate with systemic levels of IL-17. Instead, it was found to be associated with the activation of germinal center responses and the accumulation of neutrophils in the spleen. Our results demonstrate that IL-17 plays a critical role in preventing invasive disease following S. pyogenes infection of the respiratory tract.